Implementasi Teori Isnad Cum Matan dalam Hadis Seseorang yang Mempercepat Salat Karena Mendengar Tangisan Bayi - Wijayanti, Sherina; Sukmawati, Siska (Islamic Insights Journal, 2024)
This paper discusses the authenticity of the hadith of people who speed up their prayers because they hear a baby's cry based on the theory of isnad cum matan. The theory of isnad cum matan as a development of the study of sanad in hadith has received great attention from western and eastern Muslim scholars because it succeeded in breaking the premise of the previous skeptical orientalists. This paper aims to analyze the parenting hadith by trying to explore its authenticity using the isnad cum matan theory. This study focuses on how the biography of a monumental figure in the isnad cum matan theory, how the existing studies on the isnad cum matan theory, and how the application of the isnad cum matan theory in analyzing the hadith of people who speed up prayers because they hear the sound of a baby crying. The research method used is library research with a literature study approach that uses the isnad cum matan theory. This study produces, first, the hadith with the theme of people speeding up prayers because the sound of a baby's crying has a variety of narration paths, all of which tend to receive ta'dil tsiqah, shuduq, and hasan ta'dil to meet with Sa'id bin Arubah as a patrial common link. Second, the results of the matan analysis show that the variety of lafadz in matan does not affect the substance of the hadith. Third, the results of the analysis of the entire hadith show that the grace of God's love for a mother is still able to carry out congregational prayers even if she has a baby with ruksah the prayer priest hastens her prayer.